Animal models in peritoneal dialysis - NIKITIDOU, OLGA; Peppa, Vasiliki; Leivaditis, Konstantinos; Eleftheriadis, Theodoros; Zarogiannis, Sotirios G.; Liakopoulos, Vassilios (Frontiers in Physiology, 2015)
Peritoneal dialysis (PD) has been extensively used over the past years as a method of kidney replacement therapy for patients with end stage renal disease. In an attempt to better understand the properties of the peritoneal membrane and the mechanisms involved in major complications associated with PD, such as inflammation, peritonitis and peritoneal injury, both in vivo and ex vivo animal models have been used. The aim of the present review is to briefly describe the animal models that have been used, and comment on the main problems encountered while working with these models. Moreover, the differences characterizing these animal models, as well as, the differences with humans are highlighted. Finally, it is suggested that the use of standardized protocols is a necessity in order to take full advantage of animal models, extrapolate their results in humans, overcome the problems related to PD and help promote its use.